Indirect Health Policy by Sports Media: The Positive Effects of the Live Broadcast of the FIFA World Cup in the General Population - Behzad HEYDARPOUR; Ali SOROUSH; Farideh MORADI; Saeid KOMASI (Tehran University of Medical Sciences, 2019)
No Abstract###